2013
DOI: 10.2478/v10222-012-0077-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of Different Bleaching Earths for Sunflower Oil in a Pilot Plant Bleaching System

Abstract: The purpose of present study is to investigate the effi ciency of different kinds of Turkish commercial bleaching earth materials for changes in different colour pigment concentrations in neutralized sunfl ower oils. The bleaching experiments were performed in a pilot system under at stable vacuum (50 mmHg) and temperature (100ºC) for 30 min. By examining the changes in chlorophyll, β-carotene and red colour, bleaching process parameters such as type and dosage of the bleaching material were optimised. The sor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Yolk color tended to be darker in the HOSO groups than control group, may be due to the high level of pigment (β-carotene) in the diets (Table III and Fig. 1), becuase sunflower oil contains βcarotene a natural pigment [12].…”
Section: A Laying Performance and Egg Qualitymentioning
confidence: 95%
See 1 more Smart Citation
“…Yolk color tended to be darker in the HOSO groups than control group, may be due to the high level of pigment (β-carotene) in the diets (Table III and Fig. 1), becuase sunflower oil contains βcarotene a natural pigment [12].…”
Section: A Laying Performance and Egg Qualitymentioning
confidence: 95%
“…Egg and yolk were weighed using an electronic balance. Specific gravity was measured by the floating method using NaCl solutions (10,11,12,13, and 14% of NaCl) ranging in specific gravity from 1.056 to 1.083. Yolk color was measured visually by the Roche yolk color fan (F. Hoffman-La Roche Ltd., Basal, Switzerland) having 15 sample colors of ranging from 1 (the lightest) to 15 (darkest), and was scored by means of a color fan.…”
Section: B Data Recordingmentioning
confidence: 99%
“…Few studies have evaluated the content of those two families of molecules in sunflower oils as they are present in small quantities and they are eliminated during the refining process (at the bleaching step). Topkafa et al (2013) found that chlorophyll varied from 403 to 1021 ppb in four crude sunflower oils and β-carotene varied from 1692 to 2803 ppm. The refining process reduces the chlorophylls content up to 96% and 80% the β-carotene content (Kreps et al, 2014).…”
Section: Colorantsmentioning
confidence: 99%
“…This third step of the oil refining process has as main objective to remove coloring pigments from carotenoids, chlorophylls, and related compounds that catalyze the oxidation of the oil by reacting with light, by using bleaching earths that can be acid activated or coupled with activated carbon to increase the adsorption power and diminish the quantities used (Anderson, 2005;Topkafa et al, 2013). Bleaching earth are also adsorbing residual soaps, phospholipids and other polar lipids (Anderson 2005).…”
Section: Bleachingmentioning
confidence: 99%
“…In this study, the turbidity and sorption characteristics of color, chlorophyll and carotene pigments onto the clay adsorbents can be mainly discussed on the basis of Freundlich and Langmuir isotherms (Kaynak et al, 2004). The removal of the main coloring pigments (chlorophyll, β-carotene and red color) in neutralized sunflower and/or cotton oils with different types of bleaching earth materials has been examined in a pilot system at temperature of 105 ºC and pressure of 50 mmHg and bleaching earth dosage (Topallar, 1998;Ujeneza et al, 2014;Topkafa et al, 2013). Freundlich (1906) developed equation 1.1 relating adsorption to residual solute concentration.…”
Section: Adsorptive Bleachingmentioning
confidence: 99%